Algorithms for Inverse Eigenvalue Problems (Journal of Computational Mathematics, 1992)
Two new algorithms based on QR decompositions (QRDs) (with column pivoting) are proposed for solving inverse eigenvalue problems, and under some non-singularity assumptions they are both locally quadratically convergent. Several numerical tests are presented to illustrate their convergence behavior.